Experiences of patients with end stage renal disease prior to and during dialysis therapy at greater Accra regional hospital - Evans Osei Appiah; Ninon P. Amertil; Ezekiel Oti-Boadi; Peggy Georgina Intsiful; Fateimah Hakami (Taylor & Francis Group, 2022)
: Hemodialysis affects the socio-economic status of patients with end stage renal disease (ESRD) resulting in a large number of psychological disorders for both the patients and their families. The purpose of this study is to explore the experiences of patients undergoing dialysis at Greater Regional Hospital in Ghana. The researchers employed a qualitative phenomenological research design using and analyzed using Interpretive Phenomenological Analysis. A purposive sampling technique was employed by the researchers to select 16 participants who were engaged in face-to-face in-depth interviews conducted. The socio-demographic characteristics revealed that majority were males (n = 11; 69%)and more than half of the participants (n = 14; 87.5%), were over 40 years. Again, most of the participants indicated spending between 150USD to 180USD weekly on dialysis treatment alone. The study revealed 3 themes and 13 subthemes emerged from the analysis of this data. The main themes were the Physical experiences of patients prior to starting dialysis, personal experiences during dialysis and socioeconomic burden on the participants. Participants faced challenges prior to and whilst on dialysis however the symptoms were better whilst on dialysis. It is therefore recommended that participants with ESRD are supported to go through dialysis treatment to enhance their quality of life.